Task-dependent eye-movement patterns in viewing art - Nino Sharvashidze; Alexander C Schütz (Journal of Eye Movement Research)
In art schools and classes for art history students are trained to pay attention to different aspects of an artwork, such as art movement characteristics and painting techniques. Experts are better at processing style and visual features of an artwork than nonprofessionals. Here we tested the hypothesis that experts in art use different, task-dependent viewing strategies than nonprofessionals when analyzing a piece of art. We compared a group of art history students with a group of students with no art education background, while viewing 36 paintings under three discrimination tasks. Participants were asked to determine the art movement, the date and the medium of the paintings. We analyzed behavioral and eye-movement data of 27 participants. Our observers adjusted their viewing strategies according to the task, resulting in longer fixation durations and shorter saccade amplitudes for the medium detection task. We found higher task accuracy and subjective confidence, less congruence and higher dispersion in fixation locations in experts. Expertise also influenced saccade metrics, biasing it towards larger saccade amplitudes, advocating a more holistic scanning strategy of experts in all three tasks.